2013
DOI: 10.1186/1471-2431-13-205
|View full text |Cite
|
Sign up to set email alerts
|

Urinary amylase / urinary creatinine ratio (uAm/uCr) - a less-invasive parameter for management of hyperamylasemia

Abstract: BackgroundThe serum level of amylase (sAm) is commonly used as a biochemical marker for diagnosis and management of pancreatic disorders. However, the use of the urine level of amylase (uAm) is limited in practice, because the diagnostic ability of uAm is inferior to that of sAm. In the present study, the possible concordance of uAm-rerated parameters with sAm was investigated, and evaluate the usefulness of uAm for management of hyperamylasemia.MethodsFrom June 1995 to October 2009, 804 samples of both urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
3
5
0
Order By: Relevance
“…With regards to correlation analysis, urinary amylase had the best correlation with serum amylase at admission (p<0.001). In 273 samples (34.0% of all samples), when serum amylase was over the standard level, urinary amylase also had the best correlation with serum amylase (p < 0.001) [37]. The results are in accordance with the indings of the present study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…With regards to correlation analysis, urinary amylase had the best correlation with serum amylase at admission (p<0.001). In 273 samples (34.0% of all samples), when serum amylase was over the standard level, urinary amylase also had the best correlation with serum amylase (p < 0.001) [37]. The results are in accordance with the indings of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…The principles of conservative management followed in each case were adequate analgesia, correction of luid and electrolytes imbalance, complete GI tract rest and Antibiotics. Our study is consistent with the indings of Keita Terui et al, wherein the authors observed that overall conservative management is favorable over surgical management [37]. Another study done by Prakash V. Chauhan et al, wherein 38 (76%) patients were conservatively managed and only 12 (24%) were operated upon [33].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In a study done Naik et al most (92%) of the patient's serum amylase was 3 fold above normal value which is consistent with the findings of the present study. 12 Serum amylase level was again raised in 76.3% of patients studied by Terui et al 15 Similar study done by MD Wani et al, found that comparing urinary amylase levels with serum amylase level at admission in the studied subjects, it was observed that 2 patients (18.2%) had <150 U/L, 0 (0%) 150-450 U/L and 1 (0.8%) >450 U/L serum amylase levels were having <400 U/L urinary amylase levels. 2 (18.2%), 9 (47.4%) patients and 23 (19.2%) with serum amylase levels of <150, 150-450 and >450 UL were observed to have 400-1000 U/L urinary amylase levels.…”
Section: Discussionmentioning
confidence: 92%
“…Creatinine is colorless and is secreted in urine at an easily detectable level. It is a common biomarker of renal function and has been used as an indicator of urine tampering or dilution in routine drug tests as well as an internal standard for analysis of other substances such as by the analyte-creatinine ratio (12,13). In addition, urine collection is noninvasive and urine exhibits complex matrices which will help demonstrate the performance of the proposed TLC-image analysis method.…”
Section: Introductionmentioning
confidence: 99%